STUDENTS’ PERCEPTIONS OF MICROLEARNING FOR ENGLISH LEARNING IN AN ISLAMIC BOARDING SCHOOL - Hidayah, Waqiatun Nurul; Shofiya, Arina (FKIP - Universitas Tanjungpura, 2026)
The current research offers fresh insight into the context of Islamic boarding schools (pesantren), which have received limited attention in microlearning literature. It focuses on the implementation of microlearning in English learning sessions for Grade 9 students at a junior high school that enforces restricted use of digital devices. Microlearning refers to a learning approach that presents material in short, focused pieces through digital media such as brief videos, vocabulary exercises, infographics, quick quizzes, or short audio, allowing learners to study flexibly and more easily according to their needs. This research employed a qualitative descriptive design involving nine students who responded to ten open-ended questions through written-based interviews. The data were analyzed through repeated reading to gain a thorough understanding of the context of the responses, followed by assigning initial codes, grouping the codes into themes, reviewing the themes for their relevance to the findings, naming the final themes, and developing a comprehensive narrative to represent the results. The result of the research indicates that students received very limited learning support from devices because of the ban on mobile devices in the institution, making it a setback for the students' use of devices, resulting in a lack of literacy of devices' functions, which in turn led to the inability of students to analyze learning content from devices. Despite this, findings from the research indicate that students' interest in learning is highly enthusiastic toward microlearning, especially with visual supports, which clarifies that microlearning meets the requirements of students' cognitive load as well as learning interests. The research also showed that microlearning is useful when assisted by learning facilitators, because students highly count on learning facilitators' explanation on the interpretation of learning content from devices.